1996
DOI: 10.1111/j.1349-7006.1996.tb03161.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Activity of Anabolizing Enzymes in 5‐Fluorouracil‐resistant Human Stomach Cancer Cells

Abstract: The mechanism of resistance to 5‐fluorouracil (5‐FU) was studied with NUGC‐3/5FU/L, a human stomach cancer cell line which had acquired resistance as a consequence of repeated 5‐day exposures to stepwise‐increasing concentrations of 5‐FU in vitro. NUGC‐3/5FU/L was 200‐fold and over 16‐fold resistant to 96‐h and 1‐h exposures to 5‐FU, respectively. NUGC‐3/5FU/L incorporated less 5‐FU into RNA, indicating resistance to the RNA‐directed action of 5‐FU. On the other hand, NUGC‐3/5FU/L also showed resistance to in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 18 publications
2
39
0
Order By: Relevance
“…This data was concordant with in vitro and in vivo studies using a human gastric cancer cell line exposed to 5-FU. [35][36][37] Oxo decreased the levels of FUMP and 5-FU incorporated into RNA (F-RNA) by 70% only in the small intestine, while the decrease is limited to 0-20% in bone marrow and tumor regions in animal models. 38 Oxo is distributed at high levels in the digestive tract after oral administration, and thus reduces 5-FU-induced gastrointestinal toxicity, such as diarrhea, without affecting the antitumor activity of 5-FU.…”
Section: Discussionmentioning
confidence: 99%
“…This data was concordant with in vitro and in vivo studies using a human gastric cancer cell line exposed to 5-FU. [35][36][37] Oxo decreased the levels of FUMP and 5-FU incorporated into RNA (F-RNA) by 70% only in the small intestine, while the decrease is limited to 0-20% in bone marrow and tumor regions in animal models. 38 Oxo is distributed at high levels in the digestive tract after oral administration, and thus reduces 5-FU-induced gastrointestinal toxicity, such as diarrhea, without affecting the antitumor activity of 5-FU.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo studies have shown that the main origin of TS-directed FdUMP metabolite comes from the reduction of FUDP by ribonucleotide reductase after prior conversion of FU to FUDP via OPRT, but not from FUdR phosphorylated by TP (Peters et al, 1986(Peters et al, , 1991Inaba et al, 1996;Koyama et al, 2000). In this study, TP negatively correlated with the antitumour effect in patients treated with a UFT and LV regimen, which agrees with previous reports on 5-FU and LV chemotherapy (Metzger et al, 1998;Salonga et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The NUGC-3 cell line and the 5-FU-resistant NUGC-3 variant cell line, NUGC-3/5FU, were described previously. 16,17) The AGS 18) cell line was purchased from the American Type Culture Collection (ATCC). HSC-42 19,20) and KWS-1 21) cells were generously provided by Dr. Masahiko Nishiyama, Hiroshima University, and Dr. Teiichi Motoyama, Yamagata University School of Medicine, respectively.…”
Section: Methodsmentioning
confidence: 99%